Principles of digital marketing - Ilyina, V. V.; Pererva, P. G. (My University, 2023)
Іt is necessary to change the system of views on education and even the mentality; when implementing digital marketing, organizations must remember that the main value of the enterprise in the digital economy is the client, who becomes a key figure in the process of economic activity
Принципи цифрового маркетингу
Keywords: digital marketing, principles of formation, advertising, social networks; principles of formation; advertising; social networks